Bone diagenesis in the marine environment‐I: Characterization and distribution of trace elements in terrestrial mammalian bones recovered from historic shipwrecks. (25th January 2022) - Guareschi, Edda E.; Nicholls, Philip K.; Evans, Noreen J.; Barham, Milo; McDonald, Bradley J.; Magni, Paola A.; Tobe, Shanan S.
Abstract: Unlike the chemical composition and diagenetic modification of buried bones, subaqueous archaeological bone diagenesis has not been studied in detail. This observational work presents a macroscopic and microscopic characterization of 11 variably preserved archaeological terrestrial mammalian bones submerged in seawater and/or surrounded by marine sediment for 169–347 years. In situ trace element analysis was undertaken to identify geochemical fingerprints of diagenesis. The analyzed bones belong to a collection of underwater archaeological faunal materials excavated from four shipwreck sites. With one exception, all archaeological bones were fragmented, some were also heavily stained, and in two samples, the damage to the cortical layer was extensive. Bioerosion was assessed by scanning electron microscopy (SEM), and bone trace element chemistry (by laser ablation inductively coupled mass spectrometry—LA‐ICP‐MS) was compared with that of an unsubmerged modern sheep bone control. In the control, several trace elements were low in concentration (weighted mean concentration <1 ppm; Cr, Co, Ni, Cu, Y, rare earth elements, Th, U). In the submerged archaeological bones, the weighted mean concentration of Li, Cr, Cu, and U was enriched relative to the modern sheep bone, whereas Rb and Ba were depleted. The best‐preserved bone, recovered from Batavia, showed less variation in trace element patterns compared with the more poorly preserved bones. The only archaeological bone with preserved macroscopic structure and cortex showed a gradual decrease in trace element concentration from the outer surface towards the medullary cavity, whereas in samples where more cortical damage was noted, the distribution of these elements is more irregular. With the exception of Cu and Cr, the elements focused on in this work (Li, U, Rb, and Ba) are nonessential to life, supported by their low concentration in the modern sheep bone (with the exception of Ba). The results suggest that early macroscopic and microscopic diagenetic alteration influences the concentration and distribution of chemical elements in submerged bones and that in situ trace element analysis provides clues for the reconstruction of taphonomic trajectories.